Pjesme Petra Bašića o Katarini Velikoj i "turskom ratu&#34 - Dukić, Davor (Array, 2002)
Petar Bašić (1751-1814), Dubrovnik priest and writer, was one of those Croatian authors (Đuro Ferić, Blaž Bošnjak, Antun Ivanošić, Josip Stojanović, Gregur Kapucin) who celebrated in rhyme the Russian and Habsburg victories over the Ottoman army in the "Turkish war" (1787-1792). He also wrote one panegyric poem on the Russian empress Catherine the Great (Slave Katarine) and thus took part in the Russophilic Dubrovnik poetry (Ignjacije Gradić, Stjepo Rusić, Đuro Ferić). These occasional poems of Petar Bašić are preserved in only one transcription from the middle of the 19th century and are published here for the first time.